Queer in translation : sexual politics under neoliberal Islam - Savci, Evren (Perverse modernities, 2021)
"During the 2000s Turkey experienced both the rise of robust and varied LGBT movements across the country, as well as the rise to power of the "moderate Islamist" Justice and Development Party (AKP). Queer in Translation offers an ethnography of sexual politics under Turkey's AKP regime that analyzes the travel and translation of modern sexual political vocabulary during the conditions of neoliberal Islam"--